Vector Modulation by Laser and Electroabsorption Modulator With Digital Pre-coding and Pre-compensation - Ukrit Mankong (2018)
IEEE We present a method to achieve vector modulation of lightwave using an electroabsorption modulator intregrated laser. The laser section is used for direct phase modulation followed by amplitude modulation of the electroabsorption modulator section in a cascade manner, which is an alternative method to conventional IQ modulator. To allow improved phase demodulation, we propose a digital pre-compensation technique for a transmitter in optical coherent system for the first time, which includes phase-balanced differential phase shift keying encoding and digital domain pre-equalization filtering. The phase-balanced encoding technique applies parallel DC-balance coding with phase-balanced symbol mapping, which results in bounded cumulative phase and constant statistical characteristic of the modulating signal in differential M-ary phase shift keying (M-PSK) and M-ary quadrature amplitude modulation (M-QAM) formats. The digital pre-equalization filter also compensates for the phase response of the laser section. Experimental results show that the pre-digital compensation technique allows the improved complex signal demodulation compared to conventional DQPSK modulation in a back-to-back setup.